2022
DOI: 10.3390/ijms24010380
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oleuropein and Hydroxytyrosol on Inflammatory Mediators: Consequences on Inflammaging

Abstract: Aging is associated with a low-grade, systemic inflammatory state defined as “inflammaging”, ruled by the loss of proper regulation of the immune system leading to the accumulation of pro-inflammatory mediators. Such a condition is closely connected to an increased risk of developing chronic diseases. A number of studies demonstrate that olive oil phenolic compound oleuropein and its derivative hydroxytyrosol contribute to modulating tissue inflammation and oxidative stress, thus becoming attractive potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 184 publications
2
22
0
Order By: Relevance
“…The significant (p < 0.0001) reduction in the acute inflammation was characterized by the reduction of the IL-6 when treated with individual drugs (OLP, ART, CQ) and combination of OLP and ART ( Figure 10 D). 48 This reduction in the inflammation confirmed the anti-inflammatory potential of OLP as shown by the quantification of anti-inflammatory/immunoregulatory markers (IL-10) 49 ( Figure 10 E). Significantly (p < 0.001) higher secretion of IL-10 was measured when macrophages were treated with OLP at 30 μg/mL.…”
Section: Resultssupporting
confidence: 64%
“…The significant (p < 0.0001) reduction in the acute inflammation was characterized by the reduction of the IL-6 when treated with individual drugs (OLP, ART, CQ) and combination of OLP and ART ( Figure 10 D). 48 This reduction in the inflammation confirmed the anti-inflammatory potential of OLP as shown by the quantification of anti-inflammatory/immunoregulatory markers (IL-10) 49 ( Figure 10 E). Significantly (p < 0.001) higher secretion of IL-10 was measured when macrophages were treated with OLP at 30 μg/mL.…”
Section: Resultssupporting
confidence: 64%
“…However, contrasting results have been reported regarding the capability of HTyr of inhibiting inflammation mediated by monocytes/macrophages ( Table 1 ). We think that the diverse results might be related to the different experimental conditions and protocols (i.e., monocyte/macrophage experimental models, HTyr dose, times of HTyr and LPS incubations, times in which samples were taken) used by independent investigators, while Pojero et al suggested that it might depend on the timing of HTyr administration (i.e., before, during or after the incubation with LPS inflammatory stimuli) [ 97 ]. Further experiments are needed to explain these contrasting results.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols have been widely recognized as anti-inflammatory agents [ 95 , 96 , 97 , 98 , 99 , 100 ]. In addition, it has been shown by our and other’s laboratories that HTyr-enriched preparations, including those derived from EVOO and OVW, as well as multicomponent nutraceutical containing HTyr, can modulate several key processes related to inflammation [ 55 , 63 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ].…”
Section: Inflammation Inflammaging and Htyrmentioning
confidence: 99%
“…However, even at high concentrations, OLE and HT seem to be selectively cytotoxic for cancer cells, with no or negligible/minimal effects on non-cancer cells, as demonstrated for embryonic rat cardiomyoblasts H9c2(2-1), human breast epithelial cell line MCF-10A [ 41 , 93 ], nonmalignant human bronchial epithelial BEAS-2B cell line [ 35 ], normal colonic cell line CCD-841CoN [ 74 ], human normal liver cell line (HL-7702) [ 67 ], human normal prostate epithelial cells PWLE2 [ 86 ], human bile duct cell line HIBEpiC [ 69 ], human fibroblasts WI-38 [ 90 ], normal skin fibroblast cell line WS1 [ 74 ], human GN61 gingival fibroblasts [ 271 ], human lymphocytes [ 78 ], human PBMCs [ 24 , 25 ], and normal human fibroblasts [ 272 , 273 ]. Thus, OLE and HT are generally considered safe on the basis of experimental data, despite sporadic reports against the trend, as happened for HT, which proved to be toxic for human non-tumorigenic pancreas cells HPDE [ 80 ] and human normal prostate RWPE-1 cells [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both compounds have attracted attention for their accessibility, safe profile, powerful antioxidant and scavenging activity against reactive oxygen species (ROS), and controversial anti-inflammatory action. For more than two decades, OLE and HT (together or alone) have been the focus of intense research efforts in the context of infectious diseases and prevention/management of chronic non-communicable diseases, including cancer, with encouraging results from in vitro and in vivo models [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%